Paleoenvironmental potential of lacustrine sediments in the Central Highlands of Vietnam: a review on the state of research - Hướng, Nguyễn-Văn; Unkel, Ingmar; Dương, Nguyễn-Thùy; Thái, Nguyễn-Đình; Đỗ, Trọng Quốc; Đặng, Xuân Tùng; Nguyễn, Thị Hồng; Đinh, Xuân Thành; Nguyễn, Thị Ánh Nguyệt; Nguyễn, Hồng Quân; et al. (Vietnam Journal of Earth Sciences, 2023)
Global warming enhances atmospheric moisture loading and will likely affect monsoon strength in Vietnam. Without a long written history in Vietnam, we need to rely on geoarchives such as lake sediments to reconstruct past monsoon variability and regional paleoenvironmental fluctuations and evaluate current climatic trends. Natural lakes in the Central Highlands of Vietnam have the potential to have recorded shifts of the monsoon belt over glacial/interglacial cycles. Since 2016, the EOS Geoscience Research Group at Vietnam National University, Hanoi (EOS group) has collaborated with international partners to collect and analyze Vietnamese lake sediments to reconstruct the Pleistocene-Holocene climate history. Numerous sediment cores have been retrieved from Biển Hồ, Ia Bang, Ea Tyn, Ea Sno and Lak lakes between 2016 and 2022. Of special importance is a 25 m long sediment core from Biển Hồ Lake (Gia Lai province) covering the last 57 ka, which the team retrieved in April 2021. Sediment cores were analyzed for geochemistry, sedimentology, magnetic susceptibility, and radiocarbon dating. This paper reviews the status of our currently available sedimentary records to assess the paleoenvironmental potential of lacustrine sediments in the Central Highlands of Vietnam. Current data suggest that the lakes in the Central Highlands provide reliable sedimentological and geochemical records and bear the potential to reconstruct the paleoenvironmental and paleoclimatic conditions in Vietnam across several glacial periods, with a high-resolution record at least in the Holocene. The records contribute to quantifying the effects of monsoon variability and assessing the changes in hydrological conditions before and after the onset of human land use by comparing different lakes in the region. Future fieldwork will focus on retrieving longer lake sediment sequences from the Central Highlands, possibly covering the full interglacial-glacial cycle (i.e. the last 125 ka, back to MIS-5e), and on the assessment of comparable lake archives in other parts of Vietnam where the timing and character of monsoon-related climatic variations may have differed.